1998
DOI: 10.1126/science.282.5397.2261
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for IL-13 Independently of IL-4 in Experimental Asthma

Abstract: The pathogenesis of asthma reflects, in part, the activity of T cell cytokines. Murine models support participation of interleukin-4 (IL-4) and the IL-4 receptor in asthma. Selective neutralization of IL-13, a cytokine related to IL-4 that also binds to the α chain of the IL-4 receptor, ameliorated the asthma phenotype, including airway hyperresponsiveness, eosinophil recruitment, and mucus overproduction. Administration of either IL-13 or IL-4 conferred an asthma-like phenotype to nonimmunized T cell–deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

72
1,435
7
10

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,767 publications
(1,534 citation statements)
references
References 33 publications
72
1,435
7
10
Order By: Relevance
“…Since previous studies have shown that PD-L2 expression may be regulated in some cell types by Th2 cytokines or Th2 cells [21], and because asthma is believed to be a Th2-driven disease [23][24][25][26][27][28][29][30][31][32], it was of interest to examine whether PD-L2 can play a role in immune regulation in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies have shown that PD-L2 expression may be regulated in some cell types by Th2 cytokines or Th2 cells [21], and because asthma is believed to be a Th2-driven disease [23][24][25][26][27][28][29][30][31][32], it was of interest to examine whether PD-L2 can play a role in immune regulation in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic disease which can be characterized by airway hyper-responsiveness, mucus hypersecretion by goblet cells, infiltration of the airway wall with leukocytes, and elevation of serum IgE [23 24]. Studies in mouse models have established a critical role for Th2 cells, DC, Treg [24][25][26][27][28], and the Th2 type cytokines IL-4, IL-5, IL-9, and IL-13 in the asthmatic response [23,26,[29][30][31][32]. The role of the PD-1/PD-L1/PD-L2 axis in asthma is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13, a Th2-type cytokine, is a central mediator for allergic inflammation [8,9]. The blockade of IL-13 markedly inhibits allergen-induced airway hyperresponsiveness, mucus production, and eosinophilia whereas IL-13 delivery to the airway causes these effects in mice [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…these effects in mice [8][9][10][11]. Therefore, IL-13 as well as TSLP is necessary and sufficient for the development of allergic inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation